Saubhagya: An Online Food Donation Platform for Ending Hunger and Malnutrition in Sri Lanka: Author's Country: Sri Lanka (Information System; Universitas Buana Perjuangan Karawang, 2023)
Hunger and malnutrition continue to be significant challenges in developing nations, including Sri Lanka. To address this issue, the research paper presents